Canadian business corporations law - McGuinness, Kevin Patrick (LexisNexis Canada Inc., 2017)
The third edition of Kevin McGuinness's widely cited treatise on corporate law has been fully updated to take into account the significant degree of legislative development and the enormous expansion in the volume of case law which has occurred since the previous edition was published in 2007. The first volume centres on General Principles.